Currency Crises and the Real Economy : The Role of Banks - Disyatat, Piti (IMF Working Papers; Working Paper ;, 2001)
This paper shows that the quality of banks within each country is one of the important factors that can account for the fact that developing economies tend to suffer more severe output contractions in the wake of a currency crisis than more mature economies. In particular, countries with a banking sector whose balance sheets are healthy, in terms of having high net worth and low foreign currency exposure, are much less likely to suffer a contraction in the wake of an unexpected depreciation.